The frequency and amplitude of growth hormone secretory episodes as determined by deconvolution analysis are increased in adolescents with insulin dependent diabetes mellitus and are unaffected by short-term euglycaemia. - Pal, B; Matthews, D; Edge, J; Mullis, P; Hindmarsh, P; Dunger, D (1993)
OBJECTIVE: High overnight plasma growth hormone (GH) levels in insulin-dependent diabetes mellitus (IDDM) are reflected in both an increase in the GH pulse amplitude and elevated baseline GH concentrations. To determine whether these are a result of an increase in GH secretory episodes, we undertook deconvolution analysis of overnight GH profiles using previously determined half-life data. DESIGN: Deconvolution of overnight GH profiles (2000-0800 h) was undertaken from normal and diabetic adolescents (either on their usual insulin regime (n = 15), during overnight euglycaemic clamp using a variable rate insulin infusion (n = 29), or during clamp plus 100 mg pirenzepine to suppress endogenous GH (n = 7)). PATIENTS: Thirty-five normal and 29 diabetic adolescents of both sexes at all stages of puberty. MEASUREMENTS: GH secretory rates were calculated from deconvolution analysis, and Fourier transformation was increased mean overnight GH secretion when analysed by sex and by puberty stage compared to normal subjects; overnight GH secretion median (range) of diabetic group 1.88 (0.56-3.81) mU/min; control group 0.62 (0.32-1.92) mU/min (P < 0.001). Fourier transform analysis of these secretory episodes showed greater pulse frequency in the diabetics with dominant pulse periodicity of 90 minutes compared with 135 minutes in normal subjects. During overnight euglycaemia, mean +/- SEM overnight GH secretory rates were comparable to subjects' usual regime night (1.82 +/- 0.33 vs 1.91 +/- 0.37 mU/min) and there was no change in the dominant pulse periodicity of 90 minutes. Pirenzepine administration in diabetic subjects significantly reduced overnight GH secretion from 1.57 +/- 0.19 to 0.71 +/- 0.80 mU/min (P < 0.001) showing a median (range) reduction of 63 (9.3-82.8)% when compared to the subjects' clamp night. However, dominant pulse periodicity was not altered by pirenzepine administration, and remained at 90 minutes. CONCLUSION: In patients with insulin-dependent diabetes mellitus there is an increase in both the amplitude and frequency of pulsatile GH secretion compared to normal subjects, which is not affected by maintenance of overnight normoglycaemia. The anticholinergic drug pirenzepine appears to suppress the amplitude of GH pulse secretion but has no effect on frequency.